Rome Reborn - Institute for Advanced Technology in the Humanities (2008)
[Dt.:] "Rome Reborn" ist ein Projekt der Virginia Universität, das die Hauptstadt Italiens im Jahr 320 n. Chr. rekonstruiert. Etwa 7.000 Gebäude aus der damaligen Zeit sind über die Website virtuell teilweise besuchbar. Das Modell basiert auf alten Karten und Gebäudekatalogen, die detaillierte Angaben zu Apartments, Privathäusern, etc. liefern. Die Forscher konnten zudem 30 Gebäude samt Innenansicht rekonstruieren, darunter beispielsweise den Senat, die Basilica von Maxentius inklusive Freskos und Wandschmuck oder das Kolosseum. - [Engl.:] "Rome Reborn" is an international project launched in 1996 at UCLA and since 2004 based at the Institute for Advanced Technology in the Humanities (IATH). The simulation shows Rome in A.D. 320, at the time the emperor Constantine, and reconstructs some 7,000 buildings. The simulation reconstructs the interior of about 30 buildings - including the Senate, the Colosseum and the basilica built by the emperor Maxentius - complete with frescoes and decorations. Sections of the simulation are available over the website. Besides this it offers images and videos of the simulation.